Correlations between human-modified landscape structure and bird diversity in Paseh Sub-district, Sumedang District, Indonesia - SUSANTI WITHANINGSIH; MUHAMAD GALIH RAMDHANI; FIRMAN HADI; PARIKESIT PARIKESIT (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Withaningsih S, Ramdhani MG, Hadi F, Parikesit. 2025. Correlations between human-modified landscape structure and bird diversity in Paseh Sub-district, Sumedang District, Indonesia. Biodiversitas 26: 1706-1719. Various factors, including environmental conditions, human activities, and land use patterns, influence the diversity of bird species. The characteristics of each land use pattern will affect the diversity of bird species in a given area. The present study aims to investigate the correlations between human-modified landscape structures and bird diversity in the Paseh Sub-district, Sumedang District, West Java, Indonesia, highlighting how changes in land use and habitat composition influence avian species richness and distribution. Research on the relationship between bird species diversity and landscape structure in the Paseh Sub-district was conducted using the point count method for collecting bird data. Landscape structure was analyzed using Fragstats software, and the results were analyzed using Spearman correlation. The study recorded 74 bird species from 32 families, totaling 3,115 individuals. The Eurasian tree sparrow (Passer montanus) was the most abundant species, accounting for 38.1%. Bird diversity in Paseh Sub-district was assessed based on various land use patterns: settlements (H = 1.47), mixed gardens (H = 3.13), rice fields (H = 2.65), and others (H = 2.65). The overall bird species diversity was moderate (H = 2.91). The landscape influenced bird diversity. Larger areas (TA), longer edges (TE), more patches (NP, PR), complex patch shapes (MSI, MPFD), and lower landscape heterogeneity (SHDI) were correlated with higher bird species diversity.